PERAN LEMBAGA KEUANGAN SYARIAH DALAM MENINGKATKAN AKSES KEUANGAN PADA DAERAH TERPENCIL - Lestari, Wiwik Putri Eni; Susanti, Sri; Atmajayanty, Shary Agustine; Islamia, Nurul Dian (Jurnal Ekonomi & Bisnis, 2024)
Amidst the ever-growing dynamics of the global economy, financial access is a key factor in supporting the growth of a prosperous economy for society. Islamic financial institutions, with their principles rooted in Islamic values, offer a different approach to providing inclusive, fair and sustainable financial services. This article aims to discuss the important role played by Islamic financial institutions in improving financial access in remote areas. This article used a descriptive method through a qualitative approach with literature studies and descriptive analysis. The results of this study showed that Islamic financial institutions have a strategic role in increasing financial access in remote areas. Islamic financial institutions have an important role, such as providing inclusive financing, financial education, and empowering local economies, which can make a positive contribution to financial inclusion and economic growth in previously marginalized areas. This can certainly improve economic welfare and support inclusive and sustainable economic development. Thus, this study provides a deeper understanding of the important role of Islamic financial institutions in supporting economic development and financial inclusion in remote areas.